Christian types of heroism;: a study of the heroic spirit under Christianity - Adams, John Coleman (Universalist publishing house, 1891)
Introduction.--The martyrs.--The apologists.--The hermits and the monks.--The prelates and the knights.--The reformers.--The missionaries.--The philanthropists.--The statesmen.